Assessment of the type of cycling infrastructure required to attract new cyclists. October 2011. - Kingham, S.; Taylor, K.; Koorey, G. (My University, 2011)
The research, which was conducted from July 2008 to January 2010, investigated what type of cycling infrastructure would encourage new cyclists (ie people who either do not currently cycle at all, or people who do not currently cycle for utilitarian trips) to use cycling as their mode of transport for daily activities in New Zealand. It involved undertaking an international literature review followed by national surveys and Christchurch-based focus groups, to gain an understanding of some of the motivations and barriers associated with utilitarian cycling, and to evaluate a range of cycling facilities. The results show that safety was the most significant issue for potential cyclists, particularly in relation to vehicle driver behaviour and traffic volume. Other significant issues included having facilities at the destination for showering and changing, enjoyment, and the perception that car drivers are not courteous. The solutions that were most likely to effect a significant change in cycle numbers related to the nature and consistency of infrastructure, and education for motor vehicle drivers and cyclists on how to best and safely use it. The researchers recommended that along with a number of other cycling-supportive steps, planners could develop a comprehensive, consistent network of cycle-only paths with separation from motor vehicles, and with dedicated intersection facilities such as hook turns and cycle signals.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Radverkehrsförderung; Fahrradinfrastruktur; Radverkehrsanlage; Mobilitätsverhalten; Fahrradfreundliche Stadt; Motivation